Teachers’ Engagement in Bringing out the Best in Students - Rijal, Rishi Ram (Tribhuvan University Journal, 2016)
Teaching English is one of the complex and demanding matters because the teachers have to deal with the students of diverse nature, various circumstances and expectations. Like in other professions, teaching cannot be performed within the specified time. It needs much more time to be engaged in for the pre-planning, classroom delivery and post delivery reflections. In this article, the engagement of an English teacher of secondary level to bring out the best in students has been discussed in terms of his planning preparation, delivery, reflection as well as evaluation, training and collaboration with the administration and other colleagues. After the analysis of the data it has been found that English teachers in the Kathmandu valley are over busy; they do not have enough time to make planning, preparation and collaboration with the colleagues.